Optimizing Human Resource Performance in Building Construction through Technology-Enhanced Strategy Development - Husodo, Ibnu Toto; Pratikso, Pratikso; Wibowo, Kartono (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Construction projects involve complex processes requiring effective management and skilled human resources to ensure successful outcomes. This study analyzes key factors influencing human resource (HR) performance in building construction, identifying ability, working conditions, organizational structure, motivation, discipline, and compensation as critical determinants. A structured questionnaire using a 5-point Likert scale was employed as the data collection instrument, distributed to 130 contractors, with 114 valid responses collected in Semarang, Indonesia. Data analysis using SPSS v.27 confirmed that all indicators are valid, reliable, and positively perceived, with “ability” receiving the highest rating (mean = 4.8). Practical implications for project stakeholders include the need to implement targeted training, performance-based incentives, leadership development, and optimized recruitment. Technological integration is also emphasized for enhancing communication and decision-making efficiency. The findings underscore the importance of a comprehensive HR strategy that addresses both individual competencies and systemic organizational support, advancing sustainable engineering practices and improving project productivity in dynamic construction environments.